(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The word “technology” is not only used in industry, but also is used in educational system. Simply said, technique means to modernize and develop and this branch by using new teaching strategies, new methods.